Effect of Pollution Level on Size Distributions and Mixing State of Ambient Black Carbon Particles in an Urban Area during Wintertime - Kangning Li; XiaoFei Wang; Xiaohui Lu; Hong Chen; Xin Yang (Aerosol and Air Quality Research)
Abstract We deployed a Single Particle Soot Photometer (SP2) and Single Particle Aerosol Mass Spectrometer (SPAMS) to investigate the size distribution and mixing state of ambient black carbon (BC) particles in Shanghai during the winter of 2017. The mixing state of the particles changed drastically under different meteorological conditions, and higher concentrations often occurred during haze episodes. The BC particles existed in two size modes: the condensation mode, which mainly consisted of fresh traffic-emitted particles, and the droplet mode, which encompassed heavily aged traffic-emitted particles, biomass burning particles and heavy-duty diesel engine emission particles. Whereas the heavily aged traffic-emitted particles exhibited relatively small BC cores (60–80 nm in diameter) surrounded by a thick coating (100–160 nm), the biomass burning particles displayed slightly larger cores (80–130 nm) covered by an even thicker layer (160–300 nm). However, we observed a large number of particles with large cores (150–200 nm) but a relatively thin coating (40–80 nm) on clean days. Trajectory analyses of the air masses showed that they usually originated in local areas or on the North China Plain during haze episodes but mostly migrated from the East China Sea during clean episodes. Interestingly, the BC particles in the clean air masses contained V more frequently and generated intense mass spectrum signals for Ca+, suggesting that these particles probably arose from heavy machinery emissions near ports. Our real-time single particle data indicates that the sources of BC aerosol can be easily identified by measuring the size distribution and mixing state of the particles.